An investigation of integrative and independent listening test tasks in a computerised academic English test. Issue 8 (17th November 2017) - Wei, Wei; Zheng, Ying
ABSTRACT: This research provided a comprehensive evaluation and validation of the listening section of a newly introduced computerised test, Pearson Test of English Academic (PTE Academic). PTE Academic contains 11 item types assessing academic listening skills either alone or in combination with other skills. First, task analysis helped identify skills important for listening comprehension in academic settings. Aspects analysed included the purpose of assessment tasks, skills/constructs assessed, and task stimuli employed in PTE Academic. The findings indicated that modern technologies enabled PTE Academic, a computer-based test, to assess students' academic listening abilities in real time using the integration of multi-modal sources. The statistical validation consisted of two stages. Exploratory factor analysis was performed first with a sample of over 5000 students who took PTE Academic, to examine the underlying listening constructs as measured by the scores on the 11 item types item on different listening skills; these scores were subjected to Rasch analysis using CONQUEST. Second, the difficulties of the item types were estimated and the effectiveness of these item types was evaluated by calculating the information function by item type. The study has implications for test developers and test users regarding the interpretation of student performance on listening assessments.